Responding to Somali piracy by providing sustainable alternatives: addressing the motivation to offend - Lindley, Jade (Crime, law and social change, 2020)
Somali piracy is a complex issue that requires a complex series of responses on land and at sea. Existing responses, predominantly military-led, focus to reduce opportunity to offend, but from a criminological perspective, these responses fail to address the core motivators driving piracy to continue. As such, a knowledge gap exists of methods to address motivation to offend. This research fills the knowledge gap in three ways: first, it looks to routine activity theory as an underlying framework to explain the continuing motivation to commit Somali piracy. Second, it tests the existing responses to Somali piracy by critically analysing the matrix of activities in the international community’s toolkit to expose the paucity of responses that directly address motivations for offending. Third, it explores alternate non-military based responses that focus on addressing the issues driving motivations to offend, such as poverty and lack of education. This article concludes that unless meaningful and long term alternatives are available to those who may engage in piracy, it is likely to resurge.